2011
DOI: 10.1002/ange.201100299
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Directed Synthesis of Fluorescent Gold Nanoclusters: Preservation of Insulin Bioactivity and Versatility in Cell Imaging

Abstract: Ein Cluster für alle Fälle: Insulin‐Au‐Nanocluster (NCs) zeigen eine intensive rote Fluoreszenz und exzellente Biokompatibilität, und sie behalten die natürliche Bioaktivität des Insulins zur Senkung des Blutglucosespiegels bei. Mehrere Anwendungen werden demonstriert: in der Fluoreszenzbildgebung, der Röntgen‐Computertomographie und zur Untersuchung von Insulin‐Inhibitor‐Wechselwirkungen (siehe Bild; IDE=Insulin abbauendes Enzym).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 48 publications
0
108
2
Order By: Relevance
“…Scherer et al found that Au nanocolloids could be transformed into atomic AuNCs under high-temperature reflux conditions in the presence of dodecylthiol [41]. Jupally and coworkers reported a synthetic approach for the scalable synthesis of Au 130 (SR) 50 by etching withphenylethanethiol as reductant [42]. Pradeep synthesized AuNCs starting from AuNPs by pH-dependent ligand etching [43].…”
Section: Thiosmentioning
confidence: 99%
See 2 more Smart Citations
“…Scherer et al found that Au nanocolloids could be transformed into atomic AuNCs under high-temperature reflux conditions in the presence of dodecylthiol [41]. Jupally and coworkers reported a synthetic approach for the scalable synthesis of Au 130 (SR) 50 by etching withphenylethanethiol as reductant [42]. Pradeep synthesized AuNCs starting from AuNPs by pH-dependent ligand etching [43].…”
Section: Thiosmentioning
confidence: 99%
“…Tseng's group presented a novel approach for preparing highly fluorescent Au 8 NCs and Au 25 NCs by using lysozyme type VI (Lys VI) at pH 3 and pH 12, [43] respectively [49]. Inspired by this finding, researchers try to explore other proteins as efficient bioscaffolds for synthesizing AuNCs such as insulin [50], transferrin-family proteins [51,52], horseradish peroxidase [53], pepsin [54], denatured BSA [55], ribonuclease A [56], trypsin [57], DNase I [58], ovalbumin [59], and egg white [60].…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-AuNCs not only are CAs for X-ray CT and FI but also regulate blood-glucose in vivo. This bioactive structure can be applied for diabetes medicine [11].…”
Section: Bioimaging and Diagnosismentioning
confidence: 99%
“…With the rapid advance of synthesis strategies, AuNCs have been successfully employed as fluorescence labels for a variety of biological purposes, such as biomolecule detection (Huang et al 2009a;Shiang et al 2011;Jin et al 2011;Tian et al 2012), intracellular metal ion sensing (Pu et al 2011;Shang et al 2012b), live cell labeling Huang et al 2011;Liu et al 2011), cellular apoptosis studies , and targeting notorious pathogenic bacteria . Among the various applications of AuNCs, fluorescence imaging has made the most progress and attracted the greatest interest.…”
Section: Fluorescence Imaging Of Gold Nanoclusters In Vitromentioning
confidence: 99%